Correlation between Spiritual Level of Patients with Diabetes Mellitus Diabetic Wounds DM TYPE II with Development of Ankle Brachial Index (ABI) Values - Bayu Saputra; Rani Lisa Indra; Sandra; T. Abdur Rasyid (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Diabetes mellitus is a chronic disease that can cause systemic complications in the form of diabetic ulcers. One of the measures to prevent the severity of diabetic ulcers is through non-invasive measures, namely ABI (Ankle Brachial Index) examination. The condition and development of this disease can affect one of the spiritual level indicators. The purpose of this study was to determine whether there is a relationship between the spiritual care level of diabetes mellitus diabetic patients with changes in the Ancle Brachial Index value. The sample of this study was 44 people with diabetes mellitus cases who had diabetic ulcer complications. The type of research in this study was quantitative. correlative analysis. The results of the characteristics of the Russian respondents in this study were 54.3 years. The majority of respondents in this study were female, namely as many as 30 people (68.2%), secondary education level, namely as many as 19 people (43.2%), long-suffering from moderate DM 32 (72.7%) with a moderate level of spirituality 27 people (61 .4%), and a mild Ancle Brachial Index level of 22 (50.%). The results obtained from the chi-square test are p-value = 0.010, which means that the p-value is <0.05 so Ho is rejected and Ha is accepted. So it can be concluded that there is a significant relationship between the ABI value and the Spiritual level of type 2 DM sufferers.